2015
DOI: 10.3906/sag-1312-24
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of local infiltration anesthesia and peripheral nerve block:a randomized prospective study in hand lacerations

Abstract: Background/aim: To compare local infiltration anesthesia (LIA) and peripheral nerve block (PNB) in repairing hand lacerations. Materials and methods:This prospective study was designed as a randomized, controlled, unblinded trial. Fifty four patients with hand lacerations were included in the study. While 23 of these patients had LIA, PNB was performed in the remaining 31 patients. Lidocaine hydrochloride 2% and 27 gauge needles were used. Onset time of the anesthesia, response to the injection and suturing pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…79 Interestingly, the comparison of local wound infiltration (LWI) with peripheral nerve block in hand lacerations did not find any difference in terms of pain and satisfaction scores, but reported a shorter anesthesia onset time for LWI, that makes this technique, easier to perform compared to nerve block, particularly attractive in the emergency department. 81…”
Section: Upper Limb Surgerymentioning
confidence: 99%
“…79 Interestingly, the comparison of local wound infiltration (LWI) with peripheral nerve block in hand lacerations did not find any difference in terms of pain and satisfaction scores, but reported a shorter anesthesia onset time for LWI, that makes this technique, easier to perform compared to nerve block, particularly attractive in the emergency department. 81…”
Section: Upper Limb Surgerymentioning
confidence: 99%
“…There was a statistically meaningful difference September 2019, 25(3), 177-183 | 181 between patients who had received LIA and PNB, time was longer in patients who received LIA. 4 A study that compared analgesic effect of local or digital block of finger concluded that local administration of lidocaine 1% for wound anaesthesia omitted need for rescue anaesthesia. Pain caused by needle insertion, infiltration of lidocaine and suturing after local anaesthesia or digital block in finger did not differ in the study.…”
Section: Injection Of Lidocainementioning
confidence: 99%